2016
DOI: 10.1016/j.radmeas.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Rapid scan electron paramagnetic resonance at 1.0 GHz of defect centers in γ-irradiated organic solids

Abstract: The radicals in six 60Co γ-irradiated solids: malonic acid, glycylglycine, 2,6 di-t-butyl 4-methyl phenol, L-alanine, dimethyl malonic acid, and 2-amino isobutyric acid, were studied by rapid scan electron paramagnetic resonance at L-band (1.04 GHz) using a customized Bruker Elexsys spectrometer and a locally-designed dielectric resonator. Sinusoidal scans with widths up to 18.2 mT were generated with the recently described coil driver and Litz wire coils. Power saturation curves showed that the rapid scan sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Improved S/N has also been observed for irradiated teeth [36] and irradiated clipped fingernails [37], which have potential applications for radiation dosimetry. At L-band the S/N for radicals observed in γ-irradiated solids is improved by factors of 20 to 35 [30]. At 250 MHz rapid scan improves S/N relative to CW by about a factor of 10 for EPR imaging [38, 39].…”
Section: Improved Signal-to-noise For Rapid Scan Relative To Cwmentioning
confidence: 99%
“…Improved S/N has also been observed for irradiated teeth [36] and irradiated clipped fingernails [37], which have potential applications for radiation dosimetry. At L-band the S/N for radicals observed in γ-irradiated solids is improved by factors of 20 to 35 [30]. At 250 MHz rapid scan improves S/N relative to CW by about a factor of 10 for EPR imaging [38, 39].…”
Section: Improved Signal-to-noise For Rapid Scan Relative To Cwmentioning
confidence: 99%
“…[23][24][25][26] Ionizing radiation, including grays, is known to create stable radicals in a variety of chemical systems. [27][28][29][30][31][32] More recently, Blank and coworkers demonstrated that radicals are created in glucose by exposure to ionizing plasma, 33 and were able to obtain εH ≈ 150 at 3.3 T and 50 K for stationary powders. 34 Here we utilize ionizing γ-radiation as a means of generating endogenous radicals and investigate their suitability for MAS DNP.…”
mentioning
confidence: 99%
“…For example, biradical polarizing agents have been added during precipitation and/or crystallization of organic solids from solution or directly incorporated into polymers by swelling them with a radical solution or precipitating them from a radical solution. Metal centers added as dopants to organic solids , or intrinsic to inorganic materials , have also been used to hyperpolarize nuclei in the bulk. Alternatively, several early DNP studies used neutron beam irradiation to induce formation of radicals that are suitable for DNP. Ionizing radiation, including γ-rays, is known to create stable radicals in a variety of chemical systems. More recently, Blank and co-workers demonstrated that radicals are created in glucose by exposure to ionizing plasma and were able to obtain an ε H of ≈150 at 3.3 T and 50 K for stationary powders …”
mentioning
confidence: 99%
“…This magnet was designed to achieve wide magnetic field scans for L‐band (ca. 1.07 GHz) EPR spectroscopy, and in the same laboratory as the 250 MHz spectrometer, so this magnet was used for the UHF EPR spectroscopy. The parameters are given in the following list.…”
Section: Four‐coil Air‐core Magnetmentioning
confidence: 99%